KOMUNIKASI PEMBANGUNAN DALAM PEMBANGUNAN ADMINISTRASI MELALUI DIGITAL GOVERNANCE - Rani, Samsul (Alhadharah: Jurnal Ilmu Dakwah, 2017)
The role of development communications is not only a balance between central government, regional or program policies and activities that support increasing community participation, and supporting national policy, as well as private sector interests. Development communication has experienced the development of the digital era, but there is still disparity between regions in the implementation. Inequality of information systems in the development of information technology in Indonesia, has hampered the pace of development in the region. One of the forms of development communication in the digital era is the government of electronic governance (e-gov), which involves information technology and communication to improve public services and community and to increase their participation in governance of certain public sector investments. The development of gov Indonesia goes slowly and significantly, there are still many regencies / cities that have not done it yet. The main obstacle in the implementation of e-gov is the access of telecommunication networks, and internet network that is still unevenly available in various places in Indonesia